A poética urbana de Maurício Salgueiro - Rebello, Michele Cristine Marques (2013)
The objective of this thesis is to analyze the urban poetic series Urbis, produced between the 1960s and 1970s by the artist Mauricio Salgueiro. The term Urbis makes direct reference to the word city, object of study of the artist. The series is a futuris